Pernikahan Dini dalam Perspektif Sosiologi - Ach Nurhamid Awalluddin (Program Studi Hukum Keluarga Islam (HKI) dan bekerjasama dengan Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Pesantren Sunan Drajat Lamongan, 2024)
Early marriage is a significant social issue in Indonesia, considering its impact on individual and societal development. This article aims to analyze the social and cultural factors that influence early marriage and its impact from a sociological perspective. The study was conducted using a qualitative approach using literature studies. The results showed that customary norms, educational inequality, and economic pressures were the main factors causing early marriage. The impacts in question include poor reproductive health, psychological pressure, and socio-economic inequalities.